The Potential Therapeutic Agent Mepacrine Protects Caco-2 Cells against Clostridium perfringens Enterotoxin Action - John C. Freedman (American Society for Microbiology, 2017)
ABSTRACT Clostridium perfringens enterotoxin (CPE) causes the diarrhea associated with a common bacterial food poisoning and many antibiotic-associated diarrhea cases. The severity of some CPE-mediated disease cases warrants the development of potential therapeutics. A previous study showed that the presence of mepacrine inhibited CPE-induced electrophysiology effects in artificial lipid bilayers lacking CPE receptors. However, that study did not assess whether mepacrine inactivates CPE or, instead, inhibits a step in CPE action. Furthermore, CPE action in host cells is complex, involving the toxin binding to receptors, receptor-bound CPE oligomerizing into a prepore on the membrane surface, and β-hairpins in the CPE prepore inserting into the membrane to form a pore that induces cell death. Therefore, the current study evaluated the ability of mepacrine to protect cells from CPE. This drug was found to reduce CPE-induced cytotoxicity in Caco-2 cells. This protection did not involve mepacrine inactivation of CPE, indicating that mepacrine affects one or more steps in CPE action. Western blotting then demonstrated that mepacrine decreases CPE pore levels in Caco-2 cells. This mepacrine-induced reduction in CPE pore levels did not involve CPE binding inhibition but rather an increase in CPE monomer dissociation due to mepacrine interactions with Caco-2 membranes. In addition, mepacrine was also shown to inhibit CPE pores when already present in Caco-2 cells. These in vitro studies, which identified two mepacrine-sensitive steps in CPE-induced cytotoxicity, add support to further testing of the therapeutic potential of mepacrine against CPE-mediated disease. IMPORTANCE Clostridium perfringens enterotoxin (CPE) causes the gastrointestinal (GI) symptoms of a common bacterial food poisoning and several nonfoodborne human GI diseases. A previous study showed that, via an undetermined mechanism, the presence of mepacrine blocks CPE-induced electrophysiologic activity in artificial membranes. The current study now demonstrates that mepacrine also inhibits CPE-induced cytotoxicity in human enterocyte-like Caco-2 cells and that mepacrine does not directly inactivate CPE. Instead, this drug reduces both CPE pore formation and CPE pore activity in Caco-2 cells. These results suggest mepacrine as a therapeutic candidate for treating CPE-mediated GI diseases.